Celebrating 50 years of IVLA's visual literacy: reflecting on the past, present, and future. Issue 4 (2nd October 2018) - Robinson, Rhonda S.; Avgerinou, Maria D.; Pratt Curtiss, Deborah; DeVaney, Ann; Pettersson, Rune
Abstract: The International Visual Literacy Association (IVLA) celebrated its Golden Jubilee during its Annual Conference in Chicago in October 2018. The authors led an invited, blended panel session sharing their personal narratives of past and present experiences as long standing IVLA members and active visual literacists in their specific areas of study. They also offered recommendations about the future of both the IVLA and Visual Literacy, as a field of research, study and practice. The following text captures their individual perspectives and contributions.